Мікробіом ґрунту «рудого лісу»: як вплинуло забруднення радіонуклідами на структуру ґрунтової мікрофлори? - Паренюк, О.Ю.; Шаванова, К.Є.; Іллєнко, В.В.; Самофалова, Д.О.; Гудков, І.М. (Фактори експериментальної еволюції організмів, 2016)
Aim. The aim of this study is to characterize the microbiome of soil with high levels of radionuclide contamination and
figure out if its impact on microflora. Methods. Microbiome study was conducted via New Generation Sequencing. Results.
Microflora diversity was higher in samples, collected from most contaminated areas. Anyway, nutrient availability here
was higher as well so more careful study is needed to show the impact of radionuclide contamination. Acidobacteriaceae,
Microviridae, Thermomonosporaceae, and Mycobacteriaceae, were dominant in all studied samples, but the structure
of the community varied significantly. Conclusions. Soils, even subjected such extreme conditions such as radionuclide
contamination and anthropogenic transformation of terrain and vegetation, have unprecedented capabilities to maintain
and restore the structure of microbiome. However, according to our results, increased levels of radioactive contamination
lead to a significant increase in diversity, which, in our opinion, may be associated with increased evolutionary pressure
on certain individuals within the group.
Keywords: soil microflora, radionuclide contamination, Chornobyl, NGS.